Respect For Individual Limited Company (MSMEs) For Pailit Decision - Sabrina Isnintias; Moh.Saleh (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Ratification of Law Number 11 of 2020 concerning Job Creation (Job Creation Law) brings blessings to Micro, Small and Medium Enterprises (MSMEs) entrepreneurs. Because it provides convenience, protection, and empowerment to MSMEs, it is one of the objectives of the creation of the Job Creation Law which is outlined in the form of a derivative, namely Government Regulation (PP) Number 8 Year 2021. The Job Creation Law is one of the breakthroughs of the Indonesian Government to restore a sluggish economy during the Covid-19 Pandemic, many business sector sectors were hindered and suffered many losses due to the pandemic situation. The PP explains that a Limited Liability Company can be established by 1 (one) founder, specifically PT. Individuals (MSMEs), where this provision raises various questions, one of which is a form of responsibility to a third party (BANK) if PT Individuals (MSMEs) are declared In a state of bankruptcy, the purpose of this study is to identify and analyze the legal aspects of PT Perseorangan's bankruptcy settlement. The benefits of this research are addressed to individual PT directors and legal experts who face similar cases.